How to train your dragon. The hidden world [videorecording (DVD)] - Deblois, Dean; Cowell, Cressida (Universal Pictures Home Entertainment, 2019)
Now chief and ruler of Berk alongside Astrid, Hiccup has created a gloriously chaotic dragon utopia. When the sudden appearance of female Light Fury coincides with the darkest threat their village has ever faced, Hiccup and Toothless must leave the only home they've known, and journey to a hidden world thought only to exist in myth. As their true destinies are revealed, dragon and rider will fight together-to the very ends of the Earth-to protect everything they've grown to treasure.